Of People and Places: Urban Gendering in the English Plays - Kazik, Joanna (Studia Anglica Posnaniensia, 2010)
The paper examines interconnections between gender and the civic landscape in the flood pageants in the English mystery plays (York, Towneley, N-Town and Chester). The marital conflict between Noah and his wife is discussed in the context of the urban physical and spiritual world that provides a double backdrop for the play. The geometry of human sin and divine insight is analysed and textile references are investigated to reveal the spatial and professional affiliation of the characters. The silent potential of the urban setting that enriches the theatrical power of the plays and transforms the events presented on stage into a medieval interactive game between the actors and the audience is discussed.